2021
DOI: 10.3390/ijms222011059
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Gastric Hormones Ghrelin and Nesfatin-1 in Reproduction

Abstract: Ghrelin and nesfatin-1 are enteroendocrine peptide hormones expressed in rat X/A-like and human P/D1cells of the gastric mucosa. Besides their effect on food intake, both peptides are also implicated in various other physiological systems. One of these is the reproductive system. This present review illustrates the distribution of ghrelin and nesfatin-1 along the hypothalamus–pituitary–gonadal (HPG) axis, their modulation by reproductive hormones, and effects on reproductive functions as well as highlighting g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 254 publications
0
7
0
2
Order By: Relevance
“…In this research, we demonstrate that ghrelin is associated in negatively way with LDL-C, TG, HOMA-IR, and insulin as factors of insulin resistance and metabolic syndrome. The two hormones ghrelin and insulin that play a pertinent role in the regulation of the weight of the body 29 . Many studies in vivo and in vitro have shown that insulin and glucose metabolism regulate ghrelin 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In this research, we demonstrate that ghrelin is associated in negatively way with LDL-C, TG, HOMA-IR, and insulin as factors of insulin resistance and metabolic syndrome. The two hormones ghrelin and insulin that play a pertinent role in the regulation of the weight of the body 29 . Many studies in vivo and in vitro have shown that insulin and glucose metabolism regulate ghrelin 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Грелин экспрессируется в фолликулярных и гранулезных клетках яичников, ооцитах, а также продуцируется в желтом теле [46]. Его важность для оптимального созревания яичников подтверждается в исследовании с мышами, лишенными грелин-О-ацилтрансферазы, отвечающей за ацилирование грелина.…”
Section: модуляция репродуктивной функции желудочным гормоном грелиномunclassified
“…Однако, несмотря на подтверждение многими авторами способности грелина влиять на стероидогенез, данные о секреции эстрогена, тестостерона, прогестерона и простагландина яичниками в ответ на грелин довольно противоречивы. Требуются более прицельные исследования, посвященные изучению дозозависимости, основным механизмам воздействия на репродуктивную ось, особенностям его секреции [46].…”
Section: модуляция репродуктивной функции желудочным гормоном грелиномunclassified
“…The GHSR gene is widely expressed in various animal tissues and participates in the regulation of food intake, energy metabolism, cardiovascular function, cell proliferation, and reproduction [ 26 , 27 , 28 , 29 , 30 ]. Ghrelin is the endogenous ligand for GHSR and plays a role in the reproductive processes of animals [ 31 ]. The administration of ghrelin in vivo can cause changes in the morphology and structure of rat ovaries, which result in ovarian atrophy and induce cell apoptosis [ 32 ].…”
Section: Introductionmentioning
confidence: 99%